Blood-based multivariate methylation risk score for cognitive impairment and dementia - Koetsier, Jarno; Cavill, Rachel; Reijnders, Rick; Harvey, Joshua; Homann, Jan; Kouhsar, Morteza; Deckers, Kay; Köhler, Sebastian; Eijssen, Lars M. T.; van den Hove, Daniel L. A.; Demuth, Ilja; Düzel, Sandra; et al. (Alzheimer's and dementia, 2024)
Abstract INTRODUCTION The established link between DNA methylation and pathophysiology of dementia, along with its potential role as a molecular mediator of lifestyle and environmental influences, positions blood-derived DNA methylation as a promising tool for early dementia risk detection. METHODS In conjunction with an extensive array of machine learning techniques, we employed whole blood genome-wide DNA methylation data as a surrogate for 14 modifiable and non-modifiable factors in the assessment of dementia risk in independent dementia cohorts. RESULTS We established a multivariate methylation risk score (MMRS) for identifying mild cognitive impairment cross-sectionally, independent of age and sex (P = 2.0 ? 10?3). This score significantly predicted the prospective development of cognitive impairments in independent studies of Alzheimer's disease (hazard ratio for Rey's Auditory Verbal Learning Test (RAVLT)-Learning = 2.47) and Parkinson's disease (hazard ratio for MCI/dementia = 2.59). DISCUSSION Our work shows the potential of employing blood-derived DNA methylation data in the assessment of dementia risk. Highlights We used whole blood DNA methylation as a surrogate for 14 dementia risk factors. Created a multivariate methylation risk score for predicting cognitive impairment. Emphasized the role of machine learning and omics data in predicting dementia. The score predicts cognitive impairment development at the population level.